Mapping Potensi Zakat di Desa Gunung Bungsu - Evriyenni; Muksal; Analiansyah; Hasnita, Nevi; Inayatillah; Isnaliana; Cahyani, Aulia Dwi Oktavia; Zakiiya, Ghulaman (ISEI Cabang Pekanbaru, Koordinator Provinsi Riau, 2023)
Zakat management in Indonesia is regulated in Law Number 23 of 2011 concerning Zakat Management and Government Regulation (PP) Number 14 of 2014 concerning the Implementation of the Zakat Management Law. Zakat Management Institution in the Village Limited human resources and lack of managerial skills make the motivation to maximize the role of the existing Zakat Institution in Bungsu Village. For 3 days, Village Officials and the Community of Gunung Bungsu Village in XIII Koto Kampar District, Kampar Regency, Riau Province. FGD with service participants directly about economic problems, regional / natural resources potential, and the concept of zakat, as well as simulating the calculation, reporting and accounting of zakat. In addition to mentoring, it also involves expert lecturers in the field of zakat from UIN Ar Raniry Banda Aceh and from UIN Suska RIAU to provide an understanding of both fiqh, management, and application of professional management of zakat institutions